Rancang Bangun Filter Bandpass Mikrostrip Pita Sangat Lebar Berbasis Defected Ground Structure - Shita Fitria Nurjihan; Achmad Munir (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
Along with the rapid development of technology, many techniques have been employed to improve filter performance by using microstrip, one of them is using a Defected Ground Structure (DGS) technique. The DGS is a technique implemented by combining various forms of slot on the ground-plane of filter. This paper presents an ultra wideband (UWB) filter designed using DGS technique by combining two kind of slots on the ground plane, i.e., rectangular slot and rectangular ring slot. The design of composed filter is initialized using filter without DGS, then by adding two kinds of DGS on the ground plane. The DGS is used to improve S-parameter values and increase bandwidth. The method of filter design is using several parametric studies, such as changing the length of patch, width of patch, number of rectangular slot, length of rectangular slot, width of rectangular slot, and gap in rectangular ring slot. This filter is fabricated on a FR4 epoxy dielectric substrate with the thickness of 0.8 mm and the size of 27.4 mm x 22 mm. The measurement result shows that the filter could produce the working bandwidth of 4.01 GHz in the frequency range from 1.52 GHz to 5.53 GHz.